Ischemic Core and Hypoperfusion Volumes Correlate With Infarct Size 24 Hours After Randomization in DEFUSE 3. Issue 3 (March 2019) - Rao, Vaishnavi; Christensen, Søren; Yennu, Amarnath; Mlynash, Michael; Zaharchuk, Greg; Heit, Jeremy; Marks, Michael P.; Lansberg, Maarten G.; Albers, Gregory W.
Abstract : Background and Purpose—: Accurate prediction of the subsequent infarct volume early after stroke onset helps determine appropriate interventions and prognosis. In the DEFUSE 3 trial (Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke), we evaluated the accuracy of baseline ischemic core and hypoperfusion volumes for predicting infarct volume 24 hours after randomization to endovascular thrombectomy versus medical management. We also assessed if the union of baseline ischemic core and the volume of persistent hypoperfusion at 24 hours after randomization predicts infarct volume. Methods—: Patients in DEFUSE 3 with computed tomography perfusion imaging or magnetic resonance diffusion weighted imaging/perfusion imaging acquired at baseline and at 24 hours after randomization were included. Ischemic core and Tmax >6s hypoperfusion volumes at baseline and follow-up were calculated using RAPID software and compared with the infarct volumes obtained 24 hours after randomization. Patients were stratified by reperfusion status for analyses. Results—: Of 125 eligible patients, 59 patients with >90% reperfusion had a strong correlation between baseline ischemic core volume and infarct volume 24 hours postrandomization ( r =0.83; P <0.0001), and 14 patients with <10% reperfusion had a strong correlation between baseline Tmax >6s volume and infarct volume 24 hours postrandomization ( r =0.77; P <0.001). In the 52 patients with 10% to 90% reperfusion, as well as in all 125 patients, the union of the baseline ischemic core and the follow-up Tmax >6s perfusion volume was highly correlated with infarct volume 24 hours postrandomization (for N=125; r =0.83; P <0.0001), with a median absolute difference of 21.3 mL between observed and predicted infarct volumes. Conclusions—: The union of the irreversibly injured ischemic core and persistently hypoperfused tissue volumes, as identified by computed tomography perfusion or magnetic resonance diffusion weighted imaging/perfusion, predicted infarct volume at 24 hours after randomization in DEFUSE 3 patients. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02586415. Abstract : Supplemental Digital Content is available in the text.